Resveratrol inhibits TNF-α-induced inflammation to protect against renal ischemia/reperfusion injury in diabetic rats - Wang,Min (2020)
Abstract Purpose To examine effects of resveratrol on renal ischemia/ reperfusion injury (I/R) in a streptozotocin (STZ)-induced diabetic rat model. Methods Twenty-four male Sprague Dawley rats were treated with STZ injection for the development of diabetes, and divided into the following groups: Sham group, I/R group and Resveratrol group (n=8). Resveratrol (RSV) was administered at a dose of 10 mg.kg-1.d-1 fourteen days prior to suffering from I/R. Renal function, histology, SOD, MDA, TUNEL assay and expression of TNF-α, IL-1β, NF-κB-P65, COX-2 and Caspase3, Bcl2 and Bax were analyzed. Results Administration of RSV significantly reduced the serum levels of renal dysfunction and injury markers, including creatinine, blood urea nitrogen and MDA; in the other hand, it significantly increased the serum levels of SOD. The protective effect of RSV was also reflected on histologic evaluation. RSV reduced the number of apoptotic cells as determined by TUNEL assay. RSV significantly reduced the protein expression of TNF-α, IL-1β, NF-κB-P65, COX-2 and Caspase3, and Bax. Meanwhile, RSV significantly increased the protein expression of Bcl2. Conclusion RSV attenuated I/R-induced renal injury in diabetic rats through the modulation of oxidative stress and TNF-α-stimulated inflammation.